The Promise and Imperative for School Behavioral Health Research to Promote Youth Mental Health Parity - Katherine A. Perkins (Mental Health Science)
ABSTRACT In response to the call for a research agenda to eliminate youth mental health disparities, this paper presents a purposive review of five areas of promise and concern for the amelioration of disparities in school settings: (1) mental health stigma, (2) behavioral health screening and referral disparities, (3) behavioral health treatment and outcome disparities, (4) socially and culturally responsive practices, and (5) alternatives to disparity‐reproducing school discipline and carceral behavioral health systems. Each topic is placed in context with current advances in the study of multitiered systems of support (MTSS) frameworks, particularly the Interconnected Systems Framework (ISF) for integrating behavioral health personnel, expertise, and practice in schools, emphasizing the enormous opportunity and importance of school‐based behavioral health systems research for youth mental health parity. Three approaches to research are highlighted with rationale for their likelihood to contribute to both youth mental health parity and to mutually beneficial research production, use, and participation in communities: Community‐partnered research (such as community‐based participatory research), research–practice partnerships, and research–policy partnerships. Recommendations are made for congruent research, training, and funding structures necessitated by these high impact approaches.